Alumina/zirconia composite coated by biomimetic method - Pierri, Juliano; Roslindo, Eleny B.; Tomasi, Roberto; Pallone, Eliria M. J. Agnolon; Rigo, Eliana C. S. (Elsevier B.V., 2006)
In this study, a bioactive zirconia-toughened alumina (ZTA) composite was developed for orthopedic applications. This composite was obtained by slip casting of suspension powder mixtures.Biomimetic processes were used to grow a bone-like apatite layer on composite substrates using sodium silicate solution as a nucleating agent and simulated body fluids. The composites, with or without coating, were characterized by diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy and scanning electron microscopy (SEM) with energy dispersion spectroscopy (EDS), and their apparent density was determined by the Archimedes method. The composites obtained by this process possessed the expected stiffness and dimensions and their density values were similar to those of the composite's theoretical density (98.8%TD). The morphology of the hydroxyapatite formed on the composite surface was homogeneous and composed of small globules, characterizing a carbonated hydroxyapatite. The results of the tests indicated that the method employed to produce the composite and its coating was efficient under the conditions of this study. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: biomaterials; scanning electron microscopy; FTIR measurements; silicates